Demonetisation and Retail Markets: Lower Perceived Economic Effects Among Unorganized Retailers - Saji, T. G. (Indian Journal of Marketing, 2019)
This research explored the experiences of unorganized retailers in India regarding the macroeconomic effects of demonetisation in their business. Concurrently, the study evaluated the constructive effects of demonetisation in the digitalization process of the Indian economy. The temporary liquidity crunch created by the exercise caused some problems to the retailers with short-lived impacts. However, repudiating the general and political criticism against the macroeconomic implications of the demonetisation, the research acclaimed that the move was neither cost-intensive nor brought in significant economic damage to the unorganized retailing business in India. The overall impact of the demonetisation exercise in the economy was somewhat positive and contributed significantly to make the economy cashless.